How do mental health service users explain the origins and maintenance of their voice hearing: a grounded theory approach - Holt, Lucy (2013)
The current study sought to explore how, if at all, people construct an understanding of the origin and maintenance of their experience of hearing voices. An exploratory qualitative method, social constructionist grounded theory, was adopted throughout the research process. Theoretical sampling was utilised and eight participants who hear voices, or previously heard voices, and were distressed by this experience, were recruited through adult mental health teams. Each participant engaged in one digitally recorded interview.